Role of additional endobronchial biopsy in enhancing diagnostic accuracy for sarcoidosis - Tsunoda, Tomo; Oyama, Yoshiyuki; Nuki, Tomotsugu; Ito, Taisuke; Mori, Rie; Akashi, Takuro; Tsuchiya, Kazuo; Ikeda, Masaki (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and Aim: The identification of nonnecrotizing granulomas is essential for the diagnosisof sarcoidosis. For this purpose, the effectiveness of transbronchial lung biopsy (TBLB) and transbronchial needle aspiration (TBNA) is established; however, the role of endobronchial biopsy (EBB) remains uncertain. This study aimed to assess the additional diagnostic value of EBB and factors affecting its diagnostic yield for the diagnosis of sarcoidosis.Methods: This retrospective cross-sectional study included 46 patients who were preliminarily diagnosed with sarcoidosis and admitted to the Department of Respiratory Medicine of Shizuoka Saiseikai General Hospital between August 2016 and April 2023. Among them, 25 patients who underwent EBB were divided into EBB (diagnosed by EBB) and nonEBB (diagnosed by TBLB, TBNA, or clinically) groups. The patient background characteristics were analyzed to identify factors affecting the diagnostic yield of EBB.Results: The diagnostic yield of EBB alone was 24% (6 of 25 patients). There were no significant differences in the patients’ background characteristics between the two groups. When EBB was added, the diagnostic yield of TBLB increased from 47.8% to 60.9% and that of TBNA increased from 52.6% to 57.9%. In three patients, EBB alone provided histological diagnosis. Conclusions: Although EBB alone had a relatively low diagnostic yield, it led to a diagnosis in some cases. Combining TBLB or TBNA with EBB may enhance overall diagnostic yield.